MODERN DIGITAL METHODS FOR TEACHING READING SKILLS - Orazimbetov Shing’isbek; Nietullaeva Shaxsanem (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract This paper examines the role of modern digital technologies in teaching reading skills in foreign language education. The study highlights the importance of interactive platforms, electronic books, online learning applications, multimedia resources, and artificial intelligence tools in improving learners’ reading comprehension, vocabulary acquisition, and motivation. Particular attention is given to digital reading strategies, gamification, and adaptive learning systems that support individualized instruction. The paper also discusses challenges related to digital distraction, unequal access to technology, and insufficient teacher training. Based on recent international research and educational practices, practical recommendations are proposed for the effective integration of digital methods into reading instruction.